2010
DOI: 10.1074/jbc.m109.094698
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Biophysical Characterization of the Mg2+-induced 90-kDa Heat Shock Protein Oligomers

Abstract: The 90-kDa heat shock protein (Hsp90) is involved in the regulation and activation of numerous client proteins essential for diverse functions such as cell growth and differentiation. Although the function of cytosolic Hsp90 is dependent on a battery of cochaperone proteins regulating both its ATPase activity and its interaction with client proteins, little is known about the real Hsp90 molecular mechanism. Besides its highly flexible dimeric state, Hsp90 is able to self-oligomerize in the presence of divalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 42 publications
2
41
0
Order By: Relevance
“…Hsp90 is able to self-associate both in vivo [42] and in vitro in the presence of divalent-cations [42,43,47]. We previously demonstrated that the Hsp90 oligomerization process involves the dimer as the building unit to form the tetramer and hexamer and that this latter, that we named the "cozy nest", is the building block for dodecamers.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Hsp90 is able to self-associate both in vivo [42] and in vitro in the presence of divalent-cations [42,43,47]. We previously demonstrated that the Hsp90 oligomerization process involves the dimer as the building unit to form the tetramer and hexamer and that this latter, that we named the "cozy nest", is the building block for dodecamers.…”
Section: Discussionmentioning
confidence: 96%
“…As we wanted to isolate functional Hsp90:p23 complexes, all samples were prepared in the presence of the nonhydrolysable AMP-PNP nucleotide. Moreover, as Hsp90 complexes are highly dynamic, we chemically stabilized Hsp90:p23 complexes for purification purposes using our previously optimized cross-linking protocol with the zero-length EDC cross-linker [47]. The elution profile of the cross-linked p23 alone was clearly bimodal, suggesting the stabilization of p23 dimeric species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations